2015
DOI: 10.1108/pr-11-2013-0216
|View full text |Cite
|
Sign up to set email alerts
|

Job engagement and work outcomes in a cognitively demanding context

Abstract: Purpose -Job engagement has attracted much attention recently. However, very little research distinguishes between how the context may affect different engagement dimensions differently. Based on a theory of resource exhaustion, the purpose of this paper is to focus on a cognitively demanding work context in order to explore variations in effect of different engagement dimension and different expatriate work outcomes. Design/methodology/approach -The authors use survey results from 102 expatriate academics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 81 publications
4
51
0
Order By: Relevance
“…This result is similar to a study by Lauring and Selmer (2015) where absorption was found to reduce job satisfaction among expatriate academics in Singapore. On the other hand, in this study, dedication had a positive association with the same variable, and vigor was positively associated with work performance.…”
Section: Main Findingssupporting
confidence: 91%
“…This result is similar to a study by Lauring and Selmer (2015) where absorption was found to reduce job satisfaction among expatriate academics in Singapore. On the other hand, in this study, dedication had a positive association with the same variable, and vigor was positively associated with work performance.…”
Section: Main Findingssupporting
confidence: 91%
“…In addition, Na-Nan & Pukkeeree 2013found that work adjustment is the psychological state of a person, the feeling of comfort or relaxation, with the varieties of environment that are experienced. WA is a complex process involved with acculturative stress reduction (Berry, 1992), a gradual amelioration of social skills deficits (Lauring & Selmer, 2015), a recognition of expectations fitting with the new reality (Ghosh, 2013), or sometimes the culmination of a personal odyssey with a change in a philosophical worldview (Yoshikawa, 1987). A three-dimensional view of WA was proposed by Na-Nan & Pukkeeree (2013) as follows: (1) adjustment to work: a level of ability or potential according to which people are able to perform their responsibilities perfectly based on their knowledge, skills, and personality to meet the needs and expectations of the organization (Dawis & Lofquist, 1984); (2) adjustment to rules: the personal ability to accept or adapt to the organization's rules, structure, communication system, commands, and decentralization, which the employee must face in their work; and (3) adjustment to co-workers or networking (Andrews & Kacmar, 2001, Ashford & Black, 1996, Raghuram et al, 2001: the personal ability to work with or maintain independence from others in a workplace, a basic need of people who maintain social stability.…”
Section: Work Adjustmentmentioning
confidence: 99%
“…It is important to note that no exhaustive list of job demands and job resources should be made, but that the precise relevant demands and resources are contingent upon the context and characteristics of the job (Bakker and Demerouti, 2007). In the case of expatriates, job demands could, for example, be the demand of having to adjust to a foreign culture which is often associated with great emotional and cognitive costs (Lazarova et al, 2010;Ren et al, 2014;Lauring and Selmer, 2015). Job resources, on the other hand, are aspects of the job that are functional in achieving work goals and may reduce the 8 JGM 5,1 intensity of job demands.…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%